The Recently Identified Isoleucine Conjugate of cis-12-Oxo-Phytodienoic Acid Is Partially Active in cis-12-Oxo-Phytodienoic Acid-Specific Gene Expression of Arabidopsis thaliana - Arnold, Monika D; Gruber, Cornelia; Floková, Kristýna; Miersch, Otto; Strnad, Miroslav; Novák, Ondřej; Wasternack, Claus; Hause, Bettina (PloS one, 2016)
Oxylipins of the jasmonate family are active as signals in plant responses to biotic and abiotic stresses as well as in development. Jasmonic acid (JA), its precursor cis-12-oxo-phytodienoic acid (OPDA) and the isoleucine conjugate of JA (JA-Ile) are the most prominent members. OPDA and JA-Ile have individual signalling properties in several processes and differ in their pattern of gene expression. JA-Ile, but not OPDA, is perceived by the SCFCOI1-JAZ co-receptor complex. There are, however, numerous processes and genes specifically induced by OPDA. The recently identified OPDA-Ile suggests that OPDA specific responses might be mediated upon formation of OPDA-Ile. Here, we tested OPDA-Ile-induced gene expression in wild type and JA-deficient, JA-insensitive and JA-Ile-deficient mutant background. Tests on putative conversion of OPDA-Ile during treatments revealed only negligible conversion. Expression of two OPDA-inducible genes, GRX480 and ZAT10, by OPDA-Ile could be detected in a JA-independent manner in Arabidopsis seedlings but less in flowering plants. The data suggest a bioactivity in planta of OPDA-Ile.
Keywords: cyklopentany; Oxylipins; RNA, Messenger; Arabidopsis; isoleucin; listy rostlin; Cyclopentanes; Gene Expression Regulation, Plant; Isoleucine; Plant Leaves; nenasycené mastné kyseliny; regulace genové exprese u rostlin; oxylipiny; messenger RNA; ekotyp; Ecotype; Fatty Acids, Unsaturated